2012
DOI: 10.3109/01676830.2012.679170
|View full text |Cite
|
Sign up to set email alerts
|

The Method of En Face Frozen Section in Clearing Periocular Basal Cell Carcinoma and Squamous Cell Carcinoma

Abstract: Our study showed that a significant percentage of BCC and SCC lesions needed further resection after the initial frozen section edge checks to achieve clear margins. Intraoperative presence of the histopathologist increased the likelihood of achieving clearance of the cancer at a single operating session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Several optional treatments have been suggested for periorbital BCC such as chemotherapy [ 7 , 8 ], traditional surgical excision [ 9 11 ], photodynamic therapy [ 12 , 13 ], Mohs micrographic surgery [ 14 16 ], and laser ablation [ 17 – 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several optional treatments have been suggested for periorbital BCC such as chemotherapy [ 7 , 8 ], traditional surgical excision [ 9 11 ], photodynamic therapy [ 12 , 13 ], Mohs micrographic surgery [ 14 16 ], and laser ablation [ 17 – 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…MMS is said to be the "gold method" at some institutions (13,14) that previous studies showed that excision of BCC with pathological evaluation of the margins, i.e. MMS and en face FS, have the lowest relapse rates and best tissue conservation rate (14). Our results demonstrate high diagnostic accuracy, but very low sensitivity and kappa coefficient for margin evaluation with TST.…”
Section: Discussionmentioning
confidence: 54%
“…The treatment option for BCC consists of Mohs' micrographic-controlled or en face frozen section controlled surgical excision with later routine pathology sections, cryotherapy, radiotherapy and medical treatment (12). MMS is said to be the "gold method" at some institutions (13,14) that previous studies showed that excision of BCC with pathological evaluation of the margins, i.e. MMS and en face FS, have the lowest relapse rates and best tissue conservation rate (14).…”
Section: Discussionmentioning
confidence: 99%
“…98 One hundred twenty BCCs had a full-thickness eyelid ''wedge'' resection, of which 45% needed more than the standard 2 frozen sections taken to achieve clear margins. Krema and associates 99 found 94% cure rate in a series of 90 such patients. On the contrary, the suboptimal nature of the initial resections underlines the inadequacy of clinical judgment and the critical role of histological control.…”
Section: Sweat Gland Tumorsmentioning
confidence: 90%
“…98 Kvannli and associates 99 looked at the percentage of cases of BCC in which further resections were needed beyond the boundaries of the initial excision for complete tumor clearance, using the en face frozen section technique. 98 Kvannli and associates 99 looked at the percentage of cases of BCC in which further resections were needed beyond the boundaries of the initial excision for complete tumor clearance, using the en face frozen section technique.…”
Section: Sweat Gland Tumorsmentioning
confidence: 99%